1997
DOI: 10.1103/physrevb.55.5759
|View full text |Cite
|
Sign up to set email alerts
|

Breatherlike excitations in discrete lattices with noise and nonlinear damping

Abstract: We discuss the stability of highly localized, ''breatherlike,'' excitations in discrete nonlinear lattices under the influence of thermal fluctuations. The particular model considered is the discrete nonlinear Schrödinger equation in the regime of high nonlinearity, where temperature effects are included as multiplicative white noise and nonlinear damping. Numerical analysis shows that the lifetime of the breather is always finite and, in a large parameter regime, inversely proportional to the noise variance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The positive curvature of the PDF at small amplitudes indicates that the system evolves in a regime of negative temperature. A number of numerical simulations give further support to that surprising behaviour [62,328,327,186].…”
Section: Analytical Results For Dnls and Spin Systemsmentioning
confidence: 58%
“…The positive curvature of the PDF at small amplitudes indicates that the system evolves in a regime of negative temperature. A number of numerical simulations give further support to that surprising behaviour [62,328,327,186].…”
Section: Analytical Results For Dnls and Spin Systemsmentioning
confidence: 58%
“…Let us finally mention also some results obtained 21 for an extended DNLS model, which has very recently received renewed attention in the description of ultrafast catalytic electron transfer 12 . To model the interaction of an electron, or exciton, with a classical phonon system treated as a thermal bath, the DNLS equation is appended with the terms −η d dt (|ψ j | 2 ) + h j (t) ψ j , where the first term is a nonlinear damping term providing dissipation, and the second term is a fluctuation term which as a crudest approximation is taken as a Gaussian white noise.…”
Section: Breather Interactionsmentioning
confidence: 99%
“…In classical lattices, the influence of a white noise and a nonlinear damping on the stability of the breather of the discrete nonlinear Schrödinger equation has been studied [29,30]. It has been shown that the decay rate of the breather decreases as the nonlinearity increases and is proportional to the noise variance.…”
Section: Introductionmentioning
confidence: 99%